Radical radiotherapy for paediatric solid tumour metastases: an overview of current European protocols and outcomes of a SIOPE multicenter survey - Huijskens, Sophie C.; Kroon, Petra S.; Gaze, Mark N.; Gandola, Lorenza; Bolle, Stephanie; Supiot, Stephane; Abakay, Candan D.; Alexopoulou, Aikaterini; Bokun, Jelena; Chojnacka, Marzanna; Escande, Alexandre; Giralt, Jordi; et al. (European journal of cancer, 2021)
Purpose/objective - About 20% of children with solid tumours (ST) present with distant metastases (DM). Evidence regarding the use of radical radiotherapy of these DM is sparse and open for personal interpretation. The aim of this survey was to review European protocols and to map current practice regarding the irradiation of DM across SIOPE-affiliated countries. - Materials/methods - Radiotherapy guidelines for metastatic sites (bone, brain, distant lymph nodes, lung and liver) in eight European protocols for rhabdomyosarcoma, non-rhabdomyosarcoma soft-tissue sarcoma, Ewing sarcoma, neuroblastoma and renal tumours were reviewed. SIOPE centres irradiating ≥50 children annually were invited to participate in an online survey. - Results - Radiotherapy to at least one metastatic site was recommended in all protocols, except for high-risk neuroblastoma. Per protocol, dose prescription varied per site, and information on delineation and treatment planning/delivery was generally missing. Between July and September 2019, 20/27 centres completed the survey. Around 14% of patients were deemed to have DM from ST at diagnosis, of which half were treated with curative intent. A clear cut-off for a maximum number of DM was not used in half of the centres. Regardless of the tumour type and site, conventional radiotherapy regimens were most commonly used to treat DM. When stereotactic radiotherapy was used, a wide range of fractionation regimens were applied. - Conclusion - Current radiotherapy guidelines for DM do not allow a consistent approach in a multicentre setting. Prospective (randomised) trials are needed to define the role of radical irradiation of DM from paediatric ST.